Conducting International Diploma Course on Leishmaniasis and its Control in the Islamic Republic of Iran - Yaghoobi-Ershadi, Mohammad Reza; Akhavan, Amir Ahmad; Shirzadi, Mohammad Reza; Rassi, Yavar; Khamesipour, Ali; Hanafi-Bojd, Ahmad Ali; Vatandoost, Hassan (Journal of Arthropod-Borne Diseases, 2019)
Background: Leishmaniasis represents the important public health problem in the world. One of the main objectives of World Health organization is capacity building of managers and authorities who are involved with diseases control activities. Methods: The course was conducted in Esfahan Health Research and Training Center (E.H.R.T.C) in summer 2005 and 2009. The course carried out jointly by the Ministry of Health and Medical Education (MOH) of Iran, World Health Organization-Eastern Mediterranean Regional Office (WHO-EMRO) and School of Public health, Tehran University of Medical Sciences (SPH-TUMS) and designed for medical officers, senior technicians and managers involved in leishmaniasis control. Prior to initiate the course, pre-test evaluations including different subjects on leishmaniasis and its control were carried out. The examinations include multiple choice questions. The duration of the course was 3 weeks. A total of 206 contact hours were taught. The main subjects were Basic epidemiology, Leishmaniasis parasitology, Leishmaniasis entomology, control of vectors and reservoirs, principles of integrated pest management, Field work and Planning. Different methods of teaching including lecture, laboratory, workshop, team work, field exercise and presentation were used. Requirement for achievement of the course was to have at least 60% of the total mark for awarding the diploma certificate. Results: A total of 45 participants from Iraq, Afghanistan and Iran graduated from this course. Conclusion: The course is providing the skill for managers, how to combat against disease in their country and is parallel to the policy of the leishmaniasis control for capacity building in endemic areas of their countries.